2016
DOI: 10.1556/030.63.2016.015
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced survival but not amplification of Francisella spp. in the presence of free-living amoebae

Abstract: Transmission of Francisella tularensis, the etiologic agent of tularemia, has been associated with various water sources. Survival of many waterborne pathogens within free-living amoeba (FLA) is well documented; however, the role of amoebae in the environmental persistence of F. tularensis is unclear. In this study, axenic FLA cultures of Acanthamoeba castellanii, Acanthamoeba polyphaga, and Vermamoeba vermiformis were each inoculated with virulent strains of F. tularensis (Types A and B), the attenuated live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 66 publications
3
21
1
Order By: Relevance
“…This mode of survival may apply to Francisella species, especially F. tularensis . Multiple experimental studies have focused on the interaction between Francisella species and several amoeba species [145–154]. Berdal et al demonstrated that F. tularensis could penetrate in the amoeba Acanthamoeba castellanii and be released from it [152].…”
Section: Mechanisms Of F Tularensis Survival In Water Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mode of survival may apply to Francisella species, especially F. tularensis . Multiple experimental studies have focused on the interaction between Francisella species and several amoeba species [145–154]. Berdal et al demonstrated that F. tularensis could penetrate in the amoeba Acanthamoeba castellanii and be released from it [152].…”
Section: Mechanisms Of F Tularensis Survival In Water Environmentsmentioning
confidence: 99%
“…tularensis , F. tularensis subsp. holarctica and F. novicida in co-culture with amoebae such as A. castellanii , A. polyphaga , Vermamoeba vermiformis or Ochromonas danica [145,147,153]. These authors described the presence of Francisella sp.…”
Section: Mechanisms Of F Tularensis Survival In Water Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protozoa have been called the “Trojan horses of the microbial world” for their ability to promote the survival of pathogenic bacteria in the environment ( Barker and Brown, 1994 ). For example, pathogenic bacteria that have been shown to have increased survival in the environment after interactions with protozoa include Campylobacter jejuni ( Trigui et al, 2016 ; Reyes-Batlle et al, 2017 ), Francisella tularensis ( Buse et al, 2017 ), Listeria monocytogenes ( Fieseler et al, 2014 ), Legionella pneumophila ( Cervero-Arago et al, 2014 , 2015 ), Mycobacterium leprae ( Wheat et al, 2014 ), Stenotrophomonas maltophilia ( Cateau et al, 2014 ), and Yersinia enterocolitica ( Lambrecht et al, 2013 ). Although the mechanisms of increased bacterial survival are not fully understood, it has been suggested that bacteria can obtain nutrients from protozoa.…”
Section: Predation By Heterotrophic Protists Impacts Pathogens In Envmentioning
confidence: 99%
“…Due to the widespread distribution of Acanthamoeba in the nature, it can be considered an environmental reservoir for these human microbes. Furthermore, some of these bacteria surviving inside the Acanthamoeba parasites showed reduced susceptibility to some antibiotics and to disinfectants as well (Marciano-Cabral and Cabral 2003;Huws et al 2008;Buse et al 2017). Moreover, Rickettsia was found to be a symbiont of Acanthamoeba (Rowbotham 1983) that may potentially exacerbate amoebic keratitis (Taylor et al 2012).…”
Section: Free-living Amoebae and Bacteriamentioning
confidence: 99%